2021
DOI: 10.1002/pol.20210652
|View full text |Cite
|
Sign up to set email alerts
|

Gelation and yielding behavior of polymer–nanoparticle hydrogels

Abstract: Polymer-nanoparticle hydrogels are a unique class of self-assembled, shearthinning, yield-stress fluids that have demonstrated potential utility in many impactful applications. Here, we present a thorough analysis of the gelation and yielding behavior of these materials with respect to the polymer and nanoparticle component stoichiometry. Through comprehensive rheological and diffusion studies, we reveal insights into the structural dynamics of the polymer nanoparticle network that identify that stoichiometry … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 40 publications
0
36
0
Order By: Relevance
“…Previous findings show that a P:NP stoichiometric ratio between 0.1 and 1 (P:NP = 0.2 for both formulations) promotes bridging between components and thus gelation in this PNP hydrogel system; the 2:10 network likely recovers more quickly compared to the network 1:5 due to higher overall content of polymer and nanoparticles to form bridging interactions. 49…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous findings show that a P:NP stoichiometric ratio between 0.1 and 1 (P:NP = 0.2 for both formulations) promotes bridging between components and thus gelation in this PNP hydrogel system; the 2:10 network likely recovers more quickly compared to the network 1:5 due to higher overall content of polymer and nanoparticles to form bridging interactions. 49…”
Section: Resultsmentioning
confidence: 99%
“…Previous findings show that a P:NP stoichiometric ratio between 0.1 and 1 (P:NP = 0.2 for both formulations) promotes bridging between components and thus gelation in this PNP hydrogel system; the 2:10 network likely recovers more quickly compared to the network 1:5 due to higher overall content of polymer and nanoparticles to form bridging interactions. 49 Finally, the yield stress of each formulation was determined to assess the ability of the depot to retain its shape under the forces present the site of injection; it has previously been demonstrated that yield stress is an important rheological property for subcutaneous depot formation and retention. 34,50 Yield stresses of 70 and 350 Pa were measured for the 1:5 and 2:10 formulations, respectively (Figure 2e).…”
Section: Rheological Characteristics Of the Pnp Hydrogelmentioning
confidence: 99%
See 1 more Smart Citation
“…[85,86] PNP hydrogels are highly tunable viscoelastic materials, displaying useful shear-thinning and yield stress responses. [87] This enables facile clinical administration of these materials by spraying or injection directly into the required site, which is followed by the hydrogel regaining robust mechanical properties in the absence of high shear forces. As a result, the hydrogel is able to rapidly form a coating or drug depot after application.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…[40,41,42,43,44] The rheological properties of both calcium-alginate and PNP hydrogels can be easily tuned. For example, either increasing the concentration of alginate at a constant calcium content or increasing the concentration of PEG-PLA NPs at a constant HPMC-C12 concentration [45] yields hydrogels with more solid-like properties, higher yield stresses, higher preshear viscosities, and decreased creep (Figure 2b, e). By thoroughly characterizing the mechanical properties of these materials and monitoring their behavior upon subcutaneous administration in mice, we aim to elucidate relationships between rheological behaviors and the ability to form and maintain depots following injection that can yield generalizable design criteria for injectable hydrogels.…”
Section: What Hydrogel Properties Control Depot Formation?mentioning
confidence: 99%